2017
DOI: 10.5455/njppp.2017.7.0204803032017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heart rate variability in the patients suffering with chronic pain of musculoskeletal origin

Abstract: Background: Prolonged pain of musculoskeletal origin can cause changes in autonomic outflow and thereby cardiovascular system. Various studies have been conducted showing the effect of chronic pain on heart rate variability (HRV), but the same study has not been conducted in the population of Eastern Uttar Pradesh. Aims and Objectives: This study was conducted to assess the effects of chronic pain on cardiovascular autonomic control in male cases versus male controls and female cases versus female controls. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The analysis reported in [22] using HRV reveals a reduction of the parasympathetic activity and an increase of the sympathetic activity in patients with chronic pain of musculoskeletal origin.…”
Section: Pain Of Musculoskeletal Origin and Hrvmentioning
confidence: 95%
See 3 more Smart Citations
“…The analysis reported in [22] using HRV reveals a reduction of the parasympathetic activity and an increase of the sympathetic activity in patients with chronic pain of musculoskeletal origin.…”
Section: Pain Of Musculoskeletal Origin and Hrvmentioning
confidence: 95%
“…However, there is still no universal method that allows the objective evaluation of pain [22], its intensity or severity, although it may be critical in multiple conditions [28].…”
Section: Future Trends and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 20 studies, three investigated temporomandibular disorders, 25,27,28 six neck pain, [14][15][16][29][30][31] two whiplash, 32,33 one low back pain, 34 six fibromyalgia, [35][36][37][38][39][40] one fibromyalgia and temporomandibular disorders, 41 and one musculoskeletal pain. 42 Meta-analyses were not performed due to the difference in HRV protocols in terms of indexes, and positions. Most studies reported the use of electrocardiography (ECG) to obtain the RR intervals.…”
Section: Hrv Measurementmentioning
confidence: 99%